The politics of peace : Ephesians, Dio Chrysostom, and the Confucian Four books - Lau, Te-Li. (Leiden ; Boston : Brill, 2010)
Although scholarship has noted the thematic importance of peace in Ephesians, few have examined its political character in a sustained manner throughout the entire letter. This book addresses this lacuna, comparing Ephesians with Colossians, Greek political texts, Dio Chrysostoma (TM)s "Orations," and the Confucian "Four Books" in order to ascertain the rhetorical and political nature of its "topos" of peace. Through comparison with analogous documents both within and without its cultural milieu, this study shows that Ephesians can be read as a politico-religious.
Introduction to the task -- Comparison of Ephesians with Colossians -- The political in Ephesians -- The vision of peace in Dio Chrysostom -- The vision of peace in the Confucian Four books -- Comparing visions of peace.
Slightly Revision of the author's thesis (doctoral)--Emory University, 2008.
Includes bibliographical references (pages 302-334) and indexes.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; Dio, -- Chrysostom; Si shu; Dio, -- Chrysostom; Bible. -- Criticism, interpretation, etc; Si shu -- Criticism, interpretation, etc; Dio, -- Chrysostom; Bible; Si shu; Paulus (Apostel).; Dio (Chrysostomus).; Peace -- Biblical teaching; Peace -- Religious aspects; Christianity and other religions -- Confucianism; Confucianism -- Relations -- Christianity; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Christianity; Confucianism; Interfaith relations; Peace -- Biblical teaching; Peace -- Religious aspects; Friedensethik; Konfuzianismus; Electronic books; Criticism, interpretation, etc